CAPG serves as a prognostic biomarker and promotes proliferation and migration in pancreatic ductal adenocarcinoma - Zhongyu Qin; Kaixia Li; Xuanjie Li; Haorui Wang; Yiqiang Zhang (PLoS ONE, 2026)
The actin-binding protein CAPG (Capping Actin Protein, Gelsolin Like) is implicated in oncogenesis, but its role in pancreatic ductal adenocarcinoma (PDAC) remains unclear. This study combined bioinformatic analysis of TCGA/GEO datasets, immunohistochemistry on clinical samples, and functional in vitro assays to define CAPG’s significance in PDAC. We found CAPG significantly overexpressed in PDAC tissues (n = 179 tumor vs. 171 normal, p < 0.05), with levels correlating with advanced tumor stage (T3 vs. T1) and predicting poorer overall (p = 0.0085) and disease-free (p = 0.015) survival. In vitro, siRNA-mediated CAPG knockdown in PANC-1 and AsPC-1 cells markedly inhibited proliferation (CCK-8 assay) and migration (wound healing assay), and significantly sensitized cells to gemcitabine-induced apoptosis. Mechanistically, CAPG knockdown was associated with reduced ERK1/2 phosphorylation and Cyclin D1 expression, and ERK1/2 inhibition phenocopied the anti-proliferative and chemosensitizing effects. Our results establish CAPG as a negative prognostic biomarker in PDAC, demonstrate its critical role in driving proliferation and migration—potentially via modulating ERK pathway activity—and highlight its promise as a therapeutic target whose inhibition can enhance chemotherapy efficacy.